Combined and Distinct Contributions of Different Carbon Nano‐Forms in Polypropylene1. Issue 6 (10th February 2015) - Roumeli, Eleftheria; Nianias, Nikolaos; Filippousi, Maria; Avgeropoulos, Apostolos; Chrissafis, Konstantinos; Papageorgiou, Georgios Z.; Bikiaris, Dimitrios N.
<x xml:space="preserve">Abstract</x> In the present work a thorough investigation of how small amounts of multiwall carbon nanotubes (CNTs), nanodiamonds (NDs), and combinations between them affect the properties and performance of polypropylene (PP) is presented. An improvement on the mechanical properties of the nanocomposites as a consequence of the incorporation of CNTs and NDs is detected which is also related to their crystalline characteristics as well as melting and crystallization kinetics. In specific ratios, property enhancements caused by the combined incorporation of the nanofillers exceed the corresponding reinforcements induced by each type of filler separately and are probably linked with their dispersion state. The incorporation of CNTs and NDs does also increase effectively the thermal conductivity of PP, while the two fillers affect this property distinctly. The detected cumulative trends of the separate effects of the fillers confirm their distinct contributions on heat capacity and thermal diffusivity, marking a notable difference in the reinforcement mechanism of the mechanical versus thermal properties.<inline-graphic xlink:href="ark:/27927/pgjr0sjck0" content-type="mame201400419-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />